2022
DOI: 10.3390/nu14122463
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Lifestyle Recommendations for Bone Health in Older Adults with and without Osteoporosis: Cross-Sectional Results of the OUTDOOR ACTIVE Study

Abstract: Sustaining good bone health into older age is key for preventing osteoporosis. Bone health is associated with several lifestyle factors. This study investigates older adults’ adherence to bone health-promoting lifestyle recommendations dependent on osteoporosis status. Cross-sectional data of 1610 community-dwelling older adults (65–75 years) residing in Bremen, Germany (53.4% female) were included. The Osteoporosis Self-Assessment Tool and self-reported osteoporosis diagnosis were used to classify participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In a prospective study with a ten-year follow-up period on individuals with the mean age of 27 years, Baker et al reported that subjects with higher physical activity had greater BMD (Bakker et al , 2003). Physical activity improves bone health and muscle function by enhancing strength, flexibility, balance and coordination (Santos et al , 2017; Albrecht et al , 2022). In line with our results, in a study on women aged 25–65 years, Uusi-Rasi et al (1998) showed that physical activity had a greater relationship with bone mass than calcium intake.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study with a ten-year follow-up period on individuals with the mean age of 27 years, Baker et al reported that subjects with higher physical activity had greater BMD (Bakker et al , 2003). Physical activity improves bone health and muscle function by enhancing strength, flexibility, balance and coordination (Santos et al , 2017; Albrecht et al , 2022). In line with our results, in a study on women aged 25–65 years, Uusi-Rasi et al (1998) showed that physical activity had a greater relationship with bone mass than calcium intake.…”
Section: Discussionmentioning
confidence: 99%
“…Women who smoke demonstrate an earlier menopause with lower serum estradiol levels 14. Consuming more than one serving of alcohol daily for females and three servings daily for males is associated with an increased osteoporotic risk 3…”
Section: Risk Factorsmentioning
confidence: 99%
“…14 Consuming more than one serving of alcohol daily for females and three servings daily for males is associated with an increased osteoporotic risk. 3 Secondary osteoporosis can occur from multiple endocrine and immune diseases that affect bone metabolism (see Causes of secondary osteoporosis). 6,[14][15][16] Diabetes mellitus is the most common secondary cause of osteoporosis, followed by medication-induced osteoporosis.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone fractures, especially in the spine and long bones, have a significant impact on patient well-being and are associated with high mortality rates. Challenges in treatment include instability, low drug effectiveness due to poor bioavailability and short half-lives, and side effects . Emerging solutions include innovative therapeutic agents, technologies like 3D printing and bone scaffolding, , finite element software for surgeries, methods to enhance bone density, , targeted drug delivery, and combined treatments …”
Section: Introductionmentioning
confidence: 99%